Prostaglandin D(2) effects and DP (1)/DP (2) receptor distribution in guinea pig urinary bladder out‐flow region - Guan, Na N. (J Cell Mol Med, 2016)
The proximal urethra and urinary bladder trigone play important roles in continence. We have previously shown that PGD (2) is released from guinea pig bladder urothelium/suburothelium and can inhibit detrusor contractile responses. We presently wished to investigate PGD (2) actions in guinea pig out‐flow region and the distribution of DP (1)/DP (2) receptors. The effects of PGD (2) on urothelium‐intact trigone and proximal urethra contractility were studied in organ bath experiments. Expression of DP (1)/DP (2) receptor proteins was analysed by western blot. Immunohistochemistry was used to identify distribution of DP (1)/DP (2) receptors. PGD (2) in a dose‐dependent manner inhibited trigone contractions induced by electrical field stimulation (EFS) and inhibited spontaneous contractions of the proximal urethra. PGD (2) was equally (trigone) or slightly less potent (urethra) compared with PGE (2). Expression of DP (1) and DP (2) receptors was found in male guinea pig bladder trigone, neck and proximal urethra. In the trigone and proximal urethra, DP (1) receptors were found on the membrane of smooth muscle cells and weak immunoreactivty was observed in the urothelium. DP (2) receptors were distributed more widespread, weakly and evenly in the urothelium and smooth muscles. Inhibitory effects by PGD (2) on motor activity of guinea pig trigone and proximal urethra are consistent with finding DP (1) and DP (2) receptors located in the urothelium and smooth muscle cells of the trigone and proximal urethra, and PGD (2) may therefore be a modulator of the bladder out‐flow region, possibly having a function in regulation of micturition and a role in overactive bladder syndrome.